The new Pretoria protocol on international interests in mining, agricultural, and construction equipment: the expansive force of the cape town convention - Rodríguez de las Heras Ballell, Teresa (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
On November 22, 2019, in the South African city of Pretoria, a fourth Protocol to the Cape Town Convention on International Interests in Mobile Equipment was adopted. The adoption of the Pretoria Protocol entails the expanding of the successful Cape Town system, as per the singular scoping formula, to the mining, agricultural, and construction industries. Thus, the Cape Town system proves an extraordinary expansive force thanks to malleable solutions, a flexible modular structure (Convention-Protocol), and, fundamentally, the harmonizing potential of its sector-specific approach, sensitive to legal traditions, but conclusive in formulating autonomous concepts and uniform solutions; and close to sectoral financing practices, suited to characteristics of equipment, and consistent with market needs. This Paper aims to provide a thorough and in-depth analysis of the Pretoria Protocol, from its elaboration to its final adoption, in the context of the Cape Town system, it belongs to, from the perspective of the balance between consistency and flexibility, the advisability to devise innovative formulae better adapted to the targeted sectors, and the need to maintain consistency with the foundational solutions of the Convention and its material and operational logic.